Young Generation Within the Framework of Religious Moderation: Building an Inclusive Religious Identity in the Digital Era - Isti Fatonah (SYAMIL: Journal of Islamic Education, 2025)
The digital era has transformed the pattern of religious identity formation among young people from physical spaces into more fluid, open, and participatory virtual environments. Social media is no longer merely a means of communication; it has become a new public sphere where the negotiation of meaning, the construction of beliefs, and the formation of socio religious affiliations take place. Through the processes of externalization, objectification, and internalization, young people’s religious identities are constructed dynamically and reflectively through symbolic interaction in digital spaces. However, social media algorithms also have the potential to create echo chambers and filter bubbles that reinforce polarization, exclusivism, and online radicalization. In this context, religious moderation serves as a normative and strategic framework for building inclusive, just, balanced, and peace-oriented religious identities. Values such as tawassuth (the middle path), tawazun (balance), i”˜tidal (justice), tasamuh (tolerance), musawah (equality), shura (deliberation), islah (reform and reconciliation), and national commitment form the foundation for maintaining social cohesion in a plural society. Strengthening religious moderation requires a multidimensional approach through digital literacy, collaboration between religious leaders and moderate influencers, the development of interfaith dialogue forums, and the integration of moderation values into educational curricula. Thus, fostering inclusive religious identities in the digital era demands educational, cultural, and structural synergy to cultivate reflective and tolerant young generations who contribute to social harmony and national unity.